Development of a national strategy with recommendations for the care of seriously ill and dying people and their relatives in pandemics: A modified Delphi study. (September 2022) - Gauder, Sonja; Pralong, Anne; Rémi, Constanze; Hodiamont, Farina; Klinger, Isabell; Heckel, Maria; Simon, Steffen T; Bausewein, Claudia
Background: The SARS-CoV-2 pandemic is a constant challenge for health care systems, also in Germany. Care of seriously ill and dying people and their relatives is often neglected and suffering increased due to sub-optimal symptom management, visiting restrictions and lonely dying. The project "Palliative Care in Pandemics (PallPan)" intended to develop a national strategy including evidence- and consensus-based recommendations for the care of seriously ill and dying people and their relatives during pandemic times in Germany. Aim: To reach consensus on evidence-based recommendations for the care of seriously ill and dying people and their relatives in pandemics. Methods: Three-step consensus process comprising two online Delphi rounds and an expert workshop conducted from April to June 2021. One hundred twenty experts from various areas of healthcare, administration, and politics in Germany were included. Results: During the consensus-process, pre-formulated evidence-based recommendations were refined step-by-step. This resulted in consensus on 33 recommendations on the topics of "supporting patients and their relatives, " "supporting staff, " and "supporting and maintaining structures and provision of palliative care." The recommendations address professional carers and various responsibilities on a governmental, federal state and municipal level, and in healthcare facilities. Conclusion: We provide evidence and consensus-based recommendations for the care of seriously ill and dying people and their relatives in pandemics in Germany. This is an important step towards a pandemic preparedness and hopefully improves the future palliative care response to pandemics.